E-Commerce Tax Regulatory Instructions in the Indonesian Government's Business Communication to Supports Social Justice - Geofakta Razali; Retno Ekasari; Nadiah Abidin; Lokita Pramesti; Endang Susanti (Yayasan Ilomata, 2022)
This research is a qualitative study that produces a conceptual understanding of how the government tries to conduct business communication in supporting the justice of conventional traders and digital entrepreneurship such as e-commerce. This study examines the efforts made in the study of e-commerce tax instructions to see the government's competence in social care, as well as making recommendations on how the instructions are carried out in order to achieve effective messages to all levels of society, especially the internal management of the government itself. It is possible, the large opportunity for digital entrepreneurship in the future to become a business alternative, if not managed properly, the subject of this research speaks through business communication theory in informative, persuasive, regulatory, and integrative to urge all parties to be aware of and comply with taxes. E-commerce taxes are a level playing field solution for the sake of harmony in the world of digital and conventional trade. The results of this study are a set of values of tax-abiding business communication on digital entrepreneurship to achieve a better socio-economic life, as well as increase the government's positive image in recognition of justice.